UNIVERSITY STUDENTS' PERCEPTIONS OF INSTAGRAM-BASED ENGLISH EDUCATIONAL ACCOUNTS FOR VOCABULARY LEARNING - Emiliana, Veril; Fitriati, Sri Wuli; Yuliati (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2026)
This study aims to explore university students' perceptions of Instagram-based English educational accounts for vocabulary learning and their role in the depth of students’ vocabulary knowledge. The topic is crucial because vocabulary mastery is still a major problem for EFL students in Indonesia. Social media can be utilized as an innovative learning platform, especially Instagram, which offers English educational accounts. Despite its potential, studies on perceptions of educational Instagram accounts and their impact on students’ vocabulary depth require further research. This study employed a qualitative descriptive design. Data were collected from 30 English major students through closed-ended questionnaires and from five selected students through semi-structured interviews. The data was analyzed using thematic analysis to identify patterns and themes in the students’ perceptions. The findings of the study indicate that most students found the English educational Instagram accounts easy to use, engaging, accessible, and useful for vocabulary learning. It also supported learning pronunciation and spelling. However, the findings revealed varied perceptions of the role of these accounts in understanding word formation. In conclusion, English educational Instagram accounts can effectively support students’ vocabulary learning, including vocabulary depth. Content related to word formation should be provided more frequently. This study contributes to the existing literature by integrating the Technology Acceptance Model with the concept of vocabulary depth. It extends the theoretical understanding of social media use in language learning. Practically, these findings can guide educators and educational content creators in designing more effective Instagram-based materials to support students’ vocabulary development.